2022
DOI: 10.1021/acs.cgd.2c01043
|View full text |Cite
|
Sign up to set email alerts
|

Improving the Stability, Dissolution, and Bioavailability of Isotretinoin by Cocrystallization

Abstract: Isotretinoin (13-cis retinoic acid, ITT) is a gold standard therapy for the treatment of severe acne. However, because of its poor absorption, ITT must be taken with fatty meals to increase bioavailability. The coadministration of food could reduce the compliance of patients and increase the risk of inconsistent serum levels because of different eating habits. In this work, we designed and synthesized four cocrystals of ITT. The cocrystal between ITT and ethyl nicotinate (ENT), namely, ITT-ENT, presented bette… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 37 publications
0
3
0
Order By: Relevance
“…Compared to the PZA monomer, 3-NPA in PZA-3-NPA cocrystals enhanced the dissolution ability of PZA, rendering PZA-3-NPA cocrystals with diverse ratios follow the similar “spring-hover” behavior in the study. However, the enhanced dissolution behavior of the cocrystals was not very obvious when compared with PZA, but the dissolution behavior of the cocrystals was still reported here based on the following consideration: First, compared to PZA, the dissolution behavior of the cocrystals was not significantly improved, but when compared with the coformer (3-NPA), the dissolution behavior of the cocrystals was strongly affected, which was contrary to the previous reports (the better the coformer property, the better the cocrystal property). , …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Compared to the PZA monomer, 3-NPA in PZA-3-NPA cocrystals enhanced the dissolution ability of PZA, rendering PZA-3-NPA cocrystals with diverse ratios follow the similar “spring-hover” behavior in the study. However, the enhanced dissolution behavior of the cocrystals was not very obvious when compared with PZA, but the dissolution behavior of the cocrystals was still reported here based on the following consideration: First, compared to PZA, the dissolution behavior of the cocrystals was not significantly improved, but when compared with the coformer (3-NPA), the dissolution behavior of the cocrystals was strongly affected, which was contrary to the previous reports (the better the coformer property, the better the cocrystal property). , …”
Section: Resultsmentioning
confidence: 99%
“…However, the enhanced dissolution behavior of the cocrystals was not very obvious when compared with PZA, but the dissolution behavior of the cocrystals was still reported here based on the following consideration: First, compared to PZA, the dissolution behavior of the cocrystals was not significantly improved, but when compared with the coformer (3-NPA), the dissolution behavior of the cocrystals was strongly affected, which was contrary to the previous reports (the better the coformer property, the better the cocrystal property). 35,36 Second, the dissolution behavior of the cocrystals reported here was used to investigate the effect of stoichiometric ratio change in pyrazinamide-3-nitrophthalic acid cocrystals (1:1, 1:2, and 2:1); it can be seen that the change in the stoichiometric ratios of pyrazinamide-3-nitrophthalic acid cocrystals displayed different dissolution behavior, given the following sequence of dissolution rate: 1:2 cocrystal > 2:1 cocrystal > 1:1 cocrystal > PZA, which was inconsistent with the Hirshfeld analysis but may be ascribed to the diverse chemical structure of these cocrystals. PXRD (Figure S3) results revealed that 1:1 PZA-3-NPA cocrystal and 1:2 PZA-3-NPA cocrystal were partially converted into pure PZA, while 2:1 PZA-3-NPA cocrystals were all transformed into pure PZA in the simulated gastric juice environment (pH = 1.2).…”
Section: Hygroscopicity Assessmentmentioning
confidence: 99%
“…The pharmaceutical cocrystal is defined as a single-phase crystalline solid composed of an active pharmaceutical ingredient (API) and coformers (CCFs) combined in the same crystal lattice through noncovalent interactions in a certain stoichiometric ratio [1][2][3][4]. The formation of cocrystals could improve the poor physicochemical properties of API without modifying the chemical structure [5][6][7][8][9][10][11][12][13][14][15][16].…”
Section: Introductionmentioning
confidence: 99%
“…15 This approach provides valuable opportunities to modulate the physicochemical properties of compounds that lack ionizable functional groups. We have previously enhanced the stability of Vitamin D 3 , 16 nicorandil, 17 and L-menthol, 18 and the bioavailability of baicalein, 19 abiraterone acetate, 20 and isotretinoin 21 through solid-state modification. Furthermore, some liquid/oily substances have been successfully converted to solids by cocrystallization.…”
Section: Introductionmentioning
confidence: 99%